I dati INVALSI per indagare alcune caratteristiche degli studenti italiani III Seminario "I dati INVALSI: uno strumento per la ricerca" - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
One of the main school goals is to assist all students in pursuing a common core of basic targets, with respect for each pupil's ways of learning, especially for the ones who have any special educational need. This book collects papers, submitted at III edition of the Seminar "INVALSI data: a research tool" held in Bari from 26th to 28th October 2018, in order to investigate Italian students' features, such as gender, migrant and socio-economic-cultural backgrounds. Thanks to INVALSI data, researchers and teachers can shed light on differences and similarities among students about their school results and academic achievement. As a Statistical Service, we hope chapters of this could be a useful tool for school research.